IMPLICATIONS OF ANTIMICROBIAL STEWARDSHIP IN A PUBLIC HOSPITAL - Alves Araújo, Layla (2024)
To describe the clinical and financial implications of the strategies of an Antimicrobial Stewardship Programme (AMP) in the adult and paediatric wards and Intensive Care Units (ICUs) of a public hospital in the state of Ceará. This was a prospective, descriptive and quantitative study of the implications of the recommendations made by the AMP team between June and October 2023. Data was collected from electronic medical records and patient files monitored by the programme. The clinical significance, acceptability rate and minimised cost of the recommended strategies were analysed. 1165 recommendations were made in 553 patients, with stopping treatment (25.24%) being the most common type of recommendation, followed by dose adjustment (22.83%). Reducing unnecessary exposure to antimicrobials (42.40 per cent) and increasing treatment efficacy (32.79 per cent) stood out as the most common clinical impacts. Recommendations were the most important in 50.47 per cent of cases. The minimising strategies resulted in net cost savings of approximately R$115,843.75. The team's recommendations had a positive influence on both the clinical and financial results of antimicrobial use.